An Analysis of Xueda Education’s Financial Performance in the Context of Covid-19 - Chen, Ziyun (Pacific International Journal, 2023)
The Covid-19 pandemic has had a significant impact on large enterprises in China, resulting in closures and staff layoffs, which have negatively affected the training education industry. This paper presents a case study of Xueda Education, a listed company, to analyze its financial situation from 2017-2020, the first three years of the pandemic, and 2020-2023, another three years of the pandemic. The study uses financial indicators to discuss the development problems of training education in terms of profitability, development capacity, solvency, and operating capacity. A side-by-side comparison method is used to compare Xueda Education’s financial performance with two other companies in the same field. The study concludes that Xueda Education’s profitability, development capacity, solvency, and operating capacity decreased, especially in terms of operating capacity. The short-term solvency of the debt servicing capacity decreased, while the long-term solvency capacity did not change significantly. The study proposes solutions for improving the financial risk system and finding new ways to sustain the company. This paper provides valuable insights for policymakers and researchers in the training education industry to address the impact of Covid-19 on enterprises and the industry.